Peran Guru PAI di dalam Penanggulangan Kenakalan Siswa - Abdul Muis; Wedi Samsudi (Fakultas Tarbiyah, Universitas Ibrahimy, 2022)
There are various kinds of problems found in schools such as students againsts rules and so on. These problems need to be resolved properly by all schoolcomponents, for example through teacher guidance. The role of the PAI teacheris the creation of a series of interrelated behaviors in a particular situation as well as the formation of morals that focus on the formation of conscience and thecultivation of divine qualities through education and teaching with varioussciences. PAI teachers have an important role in dealing with student of ense. This role is like providing advice and guidance that emphasizes the formation ofmorals and the cultivation of divine qualities through the educational process. Students' delinquency can be overcome with the professional duties of teachers, namely educating, developing students' personalities, developing intellectually, managing order, human tasks in accordance with human dignity and sociald guiding students to become good citizens.There are various kinds of problems found in schools such as students againstschool rules and so on. These problems need to be resolved properly by all schoolcomponents, for example through teacher guidance. The role of the PAI teacheris the creation of a series of interrelated behaviors in a particular situation as well as the formation of morals that focus on the formation of conscience and thecultivation of divine qualities through education and teaching with variouss PAI teachers have an important role in dealing with student of ense. This role is like providing advice and guidance that emphasizes the formation ofmorals and the cultivation of divine qualities through the educational process. Students' delinquency can be overcome with the professional duties of teachers, namely educating, developing students' personalities, developing intellectually, managing order, human tasks in accordance with human dignity and socialduties, guiding students to become good citizens.There are various kinds of problems found in schools such as students againstschool rules and so on. These problems need to be resolved properly by all schoolcomponents, for example through teacher guidance. The role of the PAI teacheris the creation of a series of interrelated behaviors in a particular situation as well as the formation of morals that focus on the formation of conscience and thecultivation of divine qualities through education and teaching with varioussciences. PAI teachers have an important role in dealing with student of ense. This role is like providing advice and guidance that emphasizes the formation ofmorals and the cultivation of divine qualities through the educational process. Students' delinquency can be overcome with the professional duties of teachers, namely educating, developing students' personalities, developing intellectually, managing order, human tasks in accordance with human dignity and socialduties, guiding students to become good citizens.